Discordant Mutations in Paired Primary and Metastatic Endometrial Adenocarcinomas Identified by Semiconductor-Based Sequencing for Rapid Cancer Genotyping. (November 2016) - Bergstrom, Colin P.; Geest, Koen De; O'Gara, Rebecca; Corless, Christopher L.; Morgan, Terry K.
Although endometrial adenocarcinoma is usually treated with surgery, patients with metastatic disease have a poor prognosis. To address the need for better treatment options, molecularly targeted drug therapies are being developed. These targeted therapies rely on accurate mutational profiling of the tumor, which is most often performed on DNA from the primary tumor. Our objective was to compare mutational concordance in primary tumors with their metastases. We genotyped 11 pairs of primary and metastatic endometrial adenocarcinomas using DNA from formalin-fixed paraffin-embedded tissue blocks and semiconductor-based next-generation sequencing. Five of these cases had multiple metastases for comparison. We sequenced 37 known cancer genes that are targets for new drug therapies. A total of 62 mutations were identified in 16 of these 37 genes. The most common mutations were in PIK3CA and PTEN. Overall, there was a 53% discordance in mutations between primary tumors and their paired (33 of 62). The absence of mutations in metastases (25 of 33, 76%) compared with the primary neoplasm was more common than gain of mutations (8 of 33, 24%). There was a 15% discordance rate between paired metastases within individuals (6 of 40), which was significantly less frequent than the rate between primary tumors and their metastases (Fisher exact P value <.0001). Although the sample size is relatively small, our data suggest it may be prudent to test metastases, rather than the primary neoplasm, when using molecularly targeted drug therapies, because isolated metastases may lack mutations detected in the heterogeneous mixture of the tumor's origin.